Upaya Peningkatan Perkembangan Bahasa melalui Metode Role Play bagi Anak Tunagrahita di SLBN Pembina Mataram - Eka Adithia Pratiwi; Misroh Mulianingsih; Fitri Romadonika; Supriyadi Supriyadi (LPPM Universitas Bumigora, 2021)
Mentally retarded children are children who have intelligence below the average that occurs during development and have obstacles in adaptive assessment. The language development of mentally retarded children is basically lower than that of children in general, most children cannot achieve perfect language skills, language development is very lagging compared to children in general, even at the same Mental Age. Talking activities are very important for mild type mentally retarded students, because the potential for mild-type mentally retarded students to speak can still be maximally optimized, by speaking, students can communicate formally with the teacher during activities teaching and learning is carried out in the classroom. The goal is to improve language skills in mentally retarded children. The method of implementing activities using Role Play method. The results before the intervention of 5 samples of speech ability in the moderate category of 3 people (83.3%), and in the poor category as many as 2 people (16.7%), after getting the intervention speaking ability in the good category 2 people (40%), enough 3 people (60%). So it can be concluded that there is an increase in language skills in children with mild mental retardation.